PENGGUNAAN MEDIA GAMBAR BERGERAK UNTUK MENINGKATKAN PENGUASAAN MUFRODAT BAHASA ARAB SISWA KELAS VII PONDOK PESANTREN ISLAM TERPADU AL-HUDA WONOGIRI - Adhimas Dwi Permana (Walada: Journal of Primary Education, 2026)
This study aims to improve students’ Arabic vocabulary (mufrodat) mastery through the use of animated visual media among seventh-grade students at Pondok Pesantren Islam Terpadu (PPIT) Al-Huda Wonogiri. This research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles. The subjects of this study were 20 students. Data collection techniques included tests, observations, and documentation. The results indicated a significant improvement in students’ vocabulary mastery. The mean score increased from 64.6 in the pre-action stage to 72.4 in Cycle I, and further improved to 81.6 in Cycle II. Additionally, the classical learning completeness reached 80% in Cycle II. The improvement was also reflected in students’ increased participation, motivation, and confidence during the learning process. These findings demonstrate that animated visual media is effective in enhancing Arabic vocabulary mastery, as it provides more concrete, engaging, and interactive learning experiences. The integration of visual and auditory elements helps students understand vocabulary contextually. Therefore, animated visual media can serve as an innovative instructional strategy to improve the quality of Arabic language learning, particularly in vocabulary acquisition